2022
DOI: 10.1128/jvi.00755-22
|View full text |Cite
|
Sign up to set email alerts
|

SUMO Modification of Histone Demethylase KDM4A in Kaposi’s Sarcoma-Associated Herpesvirus-Induced Primary Effusion Lymphoma

Abstract: PEL is an aggressive and untreatable B-cell lymphoma caused by KSHV infection. Therefore, new therapeutic approaches for PEL need to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Once KDM4A has lost its acetylation modi cation, it is degraded by the E3 ubiquitin ligase SYVN1. sumo modi cation of KDM4A has also been reported, and sumo modi cation of KDM4A is essential for primary effusion lymphoma caused by Kaposi sarcoma-associated herpes virus [31]. These studies indicate the importance of posttranslational modi cation of KDM4A protein.…”
Section: Discussionmentioning
confidence: 64%
“…Once KDM4A has lost its acetylation modi cation, it is degraded by the E3 ubiquitin ligase SYVN1. sumo modi cation of KDM4A has also been reported, and sumo modi cation of KDM4A is essential for primary effusion lymphoma caused by Kaposi sarcoma-associated herpes virus [31]. These studies indicate the importance of posttranslational modi cation of KDM4A protein.…”
Section: Discussionmentioning
confidence: 64%
“…Apart from physiological functions, KDM4A is also involved in modulating several non-cancer diseases by regulating different downstream genes ( Table 2 ), such as cardiac hypertrophy, 21 atherosclerosis, 22 microbial infection, 23 , 24 , 25 , 43 SLE, 19 ischemic stroke, 44 vascular inflammation, 20 , 45 liver fibrosis, 21 and mood disorders. 46 Four-and-a-half LIM domain 1 (FHL1) is a key component of the mechano-transducer machinery in the heart, and KDM4A can occupy the FHL1 promoter in response to transverse aortic constriction and up-regulate FHL1 levels by removing methyl groups from H3K9me3 during cardiac hypertrophy.…”
Section: The Structure and Function Of Kdm4amentioning
confidence: 99%
“… 25 , 26 Further study indicated that SUMOylated KDM4A is required for the survival, movement, and angiogenesis of lytic KSHV-infected primary effusion lymphoma cells by modulating IL-10 levels. 43 In addition, KDM4A also regulates the replication of human T-cell lymphotropic virus 1 (HTLV-1) and human papillomavirus (HPV) via interaction with H3K36me3 and retinoblastoma protein (pRb), respectively. 24 , 47 In SLE, depletion of KDM4A and KDM4C potentiates B-cell activation and proliferation in response to T follicular helper cell-derived signals by reducing the levels of the cell cycle inhibitors Cdkn2c and Cdkn3.…”
Section: The Structure and Function Of Kdm4amentioning
confidence: 99%
“…Currently, the most widely employed sequencing techniques include three next-generation sequencing (NGS) systems (i.e., Illumina, Ion Torrent, BGI) and two third-generation sequencing techniques (i.e., PacBio and Nanopore) [41]. These sequencing approaches are the basis for the development of a variety of genomic and transcriptomic research methodologies, including DNA sequencing [15], RNA sequencing [42], 16S rRNA sequencing [43], epigenetic techniques (e.g., ChIP-seq and DNA/RNA methylation sequencing) [44][45][46], and three-dimensional genomic technologies [47]. Moreover, recent research advances of gene editing tools have enabled multi-gene manipulation on a genome-wide level [48].…”
Section: Genomics and Transcriptomics For Tumor Microbiome Studiesmentioning
confidence: 99%